2021
DOI: 10.1097/rlu.0000000000003837
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Activation Protein–Targeted PET Imaging of Metastatic Castration-Resistant Prostate Cancer Compared With 68Ga-PSMA and 18F-FDG PET/CT

Abstract: Herein we present 2 mCRPC (metastatic castration-resistant prostate cancer) patients who underwent 68Ga-PSMA PET/CT for PSMA-targeted radioligand therapy eligibility. Prior studies have noted aggressive clinical behavior and poor prognosis associated with discordant FDG positivity and low PSMA expression. Accordingly, the patients also underwent 18F-FDG PET/CT, which revealed intratumoral heterogeneity. Therefore, an additional PET/CT targeting fibroblast activation proteins (FAPs) using 68Ga-FAPI-04 was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Accordingly, these findings suggested that [ 68 Ga]Ga-FAPI-PSMA can specifically detect tumors with the high expression of FAP and PSMA with favorable imaging contrast, which may enable its utility for the diagnosis of PCa. 25 However, this research still suffers from some limitations. First, a single target may have more uniform dosimetric and pharmacokinetic profiles and thus be more amenable to clinical translation; however, the dual-targeting approach provides a default mechanism if one of the targets is unattainable in a particular lesion due to pharmacokinetics or is expressed differently from the other target during different stages of the disease.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Accordingly, these findings suggested that [ 68 Ga]Ga-FAPI-PSMA can specifically detect tumors with the high expression of FAP and PSMA with favorable imaging contrast, which may enable its utility for the diagnosis of PCa. 25 However, this research still suffers from some limitations. First, a single target may have more uniform dosimetric and pharmacokinetic profiles and thus be more amenable to clinical translation; however, the dual-targeting approach provides a default mechanism if one of the targets is unattainable in a particular lesion due to pharmacokinetics or is expressed differently from the other target during different stages of the disease.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The nature of FAP expression does not only relate to tumor cell growth and migration, but also to chronic inflammation, such as rheumatoid arthritis, heart infarction and fibroses as well as wound healing, making it rather unspecific in a mixed disease setting and at early diagnosis [22][23][24][25]. Recent studies and case reports, however, postulate FAP-positive PET/CT in PSMA negative/FDG positive disease, underlining the relevance of FAP-based imaging only in late stages and clinical aggressive tumors of the prostate [7,26,27]. In these studies, FAPI-PET performed better than PSMA-PET in advanced disease [27].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies and case reports, however, postulate FAP-positive PET/CT in PSMA negative/FDG positive disease, underlining the relevance of FAP-based imaging only in late stages and clinical aggressive tumors of the prostate [ 7 , 26 , 27 ]. In these studies, FAPI-PET performed better than PSMA-PET in advanced disease [ 27 ]. Corroborating this idea, the present study indicates the use of FAP-based diagnostics only in advanced metastatic prostate cancer or in case of doubtful lesions, therapy failure and suspected other primary tumors [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…FAP-targeted MRI-guided radiotherapy may also prove beneficial in palliative radiotherapy, particularly in reducing pain arising from PCa bone metastases, leading to improved quality of life (52). FAP-specific imaging may be most beneficial in late stage and clinically aggressive cancers, in which FAP expression can be more pronounced than PSMA and in cases with doubtful lesions, therapy failure and/or PSMA downregulation or negative disease (31,53). Patients undergoing long-term ADT may have a decreased detection sensitivity on PSMA imaging due to downregulation of the receptor, although this issue may be mitigated by ceasing ADT prior to imaging studies (54).…”
Section: Distribution Of Magnetic Nanoparticles In Tissuesmentioning
confidence: 99%